2009
DOI: 10.1111/j.1440-1746.2009.05872.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum aminotransferase activity increases risk of carotid atherosclerosis in patients with non‐alcoholic fatty liver disease

Abstract: Serum ALT levels are positively associated with the risk of carotid atherosclerosis in patients with NAFLD, suggesting that serum ALT levels could serve as a surrogate marker of cardiovascular risk in this special clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 27 publications
4
40
0
1
Order By: Relevance
“…Therefore, our additional results were not able to affirm previous studies suggesting that GGT and ALT have similar or even synergistic associations with CVD and mortality risk. 4,5 Furthermore, we fully agree with Wang and Kao that the issue of alcohol intake is relevant. There is no doubt that the participants from our study region are known to be exposed to high-normal levels of alcohol intake, 6 explaining that the mean alcohol consumption in men was near the levels of risk (Ͼ20 g/day).…”
Section: Replysupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, our additional results were not able to affirm previous studies suggesting that GGT and ALT have similar or even synergistic associations with CVD and mortality risk. 4,5 Furthermore, we fully agree with Wang and Kao that the issue of alcohol intake is relevant. There is no doubt that the participants from our study region are known to be exposed to high-normal levels of alcohol intake, 6 explaining that the mean alcohol consumption in men was near the levels of risk (Ͼ20 g/day).…”
Section: Replysupporting
confidence: 67%
“…Our previous study also demonstrated that serum ALT level was positively associated with carotid atherosclerosis in patients with NAFLD, suggesting serum ALT level may predict CVD risk in patients with NAFLD. 4 Therefore, it will help us understand more about the relationship among these parameters with CVD risk and mortality if the authors could perform further analyses stratified by different serum ALT levels.Second, the present study didn't exclude participants with the habit of alcohol consumption, and the mean alcohol consumption in men was near the level of risk (20 g/day). In our clinical practice, elevated GGT level is usually observed in patients with biliary or alcoholic liver diseases that could be the major component of the top quintile GGT group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were taken in 1 g/L EDTA in morning and after 12 h fast. Blood tubes were immediately stored at 41 °C and shielded from light.…”
Section: Blood Samplesmentioning
confidence: 99%
“…Serum alanine aminotransferase (ALT) level is a well-recognized clinical marker of liver injury and may represent a consequence of the second event in the pathogenesis of NAFLD [11] . On the other hand, it has been demonstrated that augmented ALT activities can be a predictor of the development of insulin resistance, diabetes mellitus, cardiovascular diseases, and metabolic syndrome in NAFLD patients [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%